POTENSI PEMANFAATAN ICT UNTUK PENINGKATAN MUTU PEMBELAJARAN SMA DI KOTA YOGYAKARTA - Herman Dwi Surjono & Abdul Gafur (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: ICT Implementation Potentials in Public Senior High Schools inYogyakarta City to Improve the Instructional Quality. This study aims to describeICT implementation potentials for learning in terms of: (1) the level of the studentsand staffs ICT competency, (2) the model employed in implementing ICT, and (3)the obstacles in implementing ICT. This study was a descriptive study involving341 respondents consisting of students, teachers, ICT personnel, clerical staff, andprincipals. They were selected randomly from 11 public senior high schools inYogyakarta City. The quantitative data were analyzed by descriptive statistics andthe qualitative data by an inductive technique. The results show that there are 8people (2.3%) of very low level, 54 people (15.8%) of low level, 115 people (33.5%)of medium level, 128 people (37.5%) of high level, and 36 people (10.6%) of veryhigh level. ICT has been systematically implemented through design, development,utilization, management, and evaluation. The obstacles in implementing ICT comefrom the lack of personnel, infrastructure, hardware, and software.Keywords: Information and Communication Technology, ICT implementation,instructional quality.